Designing and examining polytetrafluoroethylene composites for tribotechnical purposes with activated ingredients - Berladir, Kristina; Sviderskiy, Valentin (Eastern-European Journal of Enterprise Technologies, 2016)
The influence of mechanochemical activation of matrix, fillers of various nature and composition on the structure and operating properties of polytetrafluoroethylene composites was explored. The effect of technological parameters of the process of mechanical activation on the structure, physical, mechanical and tribotechnical properties of polytetrafluoroethylene-based composites was examined. We established the modes of mechanic activation equipment for the preparation of matrix and fillers that provide for the maximum wear resistance of the composite while maintaining sufficient level of strength and we designed antifriction composites based on polytetrafluoroethylene of a new generation. Special features of developed technology for the production of composite based on polytetrafluoroethylene with the required operational properties include a preliminary separate preparation of the matrix and the fillers before their mixing by means of mechanical activation under different modes of equipment, as a result of which an increase in the indices of strength at break and wear resistance occurs. A synergistic effect of using mechanical activation of both matrix polytetrafluoroethylene and the fillers before their mixing was displayed by an increase in the indices of performance characteristics of the obtained composites: with a fibrous filler, strength at break increased by 18,6 %, relative elongation – by 28 %, wear resistance – by 6,9 times; with a dispersed filler, strength at break increased by 19,3 %, relative elongation – 27,6 %, wear resistance – by 1,7 times in comparison to the use of non-activated ingredients. The technology we developed for obtaining antifriction polytetrafluoroethylene composite of a new generation made it possible to increase wear resistance of materials by 3,7–6,0 times, strength at break – by 1,4 times compared to materials of the old generation. The rings of the compressor 4GM 2,5 U-3,4/2,8-251, made of the designed composite, allowed us to increase working resource of equipment of compressor engineering by 1,8–2,3 times.